Eco-innovations in the digital transformation of enterprises: Sustainability and competitiveness - Shafa Tiflis Aliyev; Nemtsova Elena; Paytaeva Kometa (BIO Web of Conferences)
This article explores the impact of eco-innovations on the digital transformation of enterprises, with a focus on sustainability and competitiveness. In the context of the modern digital economy, environmental innovations are becoming increasingly important for ensuring the sustainable development of enterprises. The article investigates various aspects of integrating environmental innovations into digital processes, such as resource optimization, energy consumption reduction, waste management improvement, and reducing the environmental footprint of production. Drawing on examples of best practices from various industrial sectors, the article analyzes how eco-innovations contribute to creating more sustainable and competitive enterprises in the digital era.